Stability and Electronic Properties of ON-Doped Zigzag BC2N Nanotubes - Sun*, Miao; Wu, Gonglian; Zhang, Hui; Zhang, Guiling (Asian Journal of Chemistry, 2013)
The geometry, stability and electronic properties of ON-doped zigzag (6,0), (7,0) and (8,0) BC2N nanotubes are investigated by first-principles calculations based on the density functional theory (DFT). The structures for ON-doped zigzag BC2N nanotubes remain practically the same with negligible deformations. The results show that the ON-doped (6,0) BC2N nanotubes has the lowest formation energies, especially for the B-rich environment. With the tube diameter increasing, the relative stabilities of ON-doped zigzag BC2N nanotubes are significantly weakened. For the ON-doped (6,0), (7,0) and (8,0) BC2N nanotubes, the Fermi levels are located inside the conduction band defining metallic characters. Moreover, ON-doped (6,0) and (8,0) BC2N nanotubes are direct gap semiconductors, while ON-doped (7,0) BC2N nanotubes is an indirect gap semiconductor.